2017
DOI: 10.1002/jsfa.8432
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐functional properties of sardine protein hydrolysates obtained by brewer's spent yeast and commercial proteases

Abstract: Improved biological and functional properties were observed for sardine protein hydrolysates produced using the three enzymatic treatments tested. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Due to the beneficial composition of brewery spent yeast, various microorganisms cultivated on this by-product may grow noticeably faster than other yeast types, as reported by Ferreira et al [232]. As a result, the spent yeast may be applied as a very efficient source of multiple enzymes, including proteinases [233], proteases [234,235], or pectinases [236,237]. Moreover, brewery spent yeast can be applied as nutrients during ethanol or lactic acid fermentation [238,239].…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Due to the beneficial composition of brewery spent yeast, various microorganisms cultivated on this by-product may grow noticeably faster than other yeast types, as reported by Ferreira et al [232]. As a result, the spent yeast may be applied as a very efficient source of multiple enzymes, including proteinases [233], proteases [234,235], or pectinases [236,237]. Moreover, brewery spent yeast can be applied as nutrients during ethanol or lactic acid fermentation [238,239].…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…The high pressure gave hydrolysates with higher contents of total soluble solids, total water-soluble nitrogen and trichloroacetic acid-soluble nitrogen [713]. Brewer's spent yeast proteases, Neutrase and Alcalase [714] were used to hydrolyze muscle and viscera proteins from canned sardine by-products in order to obtain products with biological and functional properties. All the treatments produced improved biological and functional properties [714].…”
Section: Comparison Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…Brewer's spent yeast proteases, Neutrase and Alcalase [714] were used to hydrolyze muscle and viscera proteins from canned sardine by-products in order to obtain products with biological and functional properties. All the treatments produced improved biological and functional properties [714].…”
Section: Comparison Of Alcalase With Other Proteasesmentioning
confidence: 99%
“…Enzyme selection also plays an important role in the emulsifying properties of FPH as it strongly influences the molecular size and hydrophobicity of the resulting peptides. Vieira et al (2017) found that sardine protein hydrolysates with alcalase yield large molecular weight peptides with excellent emulsifying stability and activity, while protease produced smaller peptides and yielded hydrolysates with very poor emulsification properties. Therefore, a low DH and a careful choice of enzymes are a key issue if enhanced emulsifying properties are desired.…”
Section: Emulsifying Propertiesmentioning
confidence: 99%